La convocatoria, las elecciones y el Congreso extraordinario de 1846 - Aguilar Rivera, José Antonio (El Colegio de México, A.C., 2011)
On January 27th, 1846, during the government of Mariano Paredes y Arrillaga, a Call was issued proposing a completely original election method to elect an extraordinary congress: to do without individual representation in order to privilege functional class interests. Not one modern representative government in the world had tried a similar system. This essay analyzes the peculiarities of this election system, describes the elections that were held on the occasion, and explores the behavior of the extraordinary constitutional congress established in June 1846 and in session until the first days of August of the same year.